A mediação alfabetizadora na produção de leitura e de escrita de gêneros e suportes textuais: o desafio de alfabetizar na perspectiva do letramento - Maria Elisa de Araujo Grossi (2008)
This research aims at analyzing the reading and writing practices under the perspective of literacy which employ authentic materials of several textual genres so as to systematize the reading and writing learning process. The key questions of this investigation came up from the researchers experience as both a kindergarten teacher and a teachers formation professor. Questions such the following were asked: Is it possible to teach reading and writing through authentic texts? Is it possible to develop literate skills while teaching reading and writing? Is it possible to develop written language skills in he context of appropriation of reading and writing skills? What sort of reading and writing practices might be developed for children who can not read and write conventionally? The theoretical support of the research is the discourse-heading perspective of language which considers language as an interactive process between speakers. Reading and writing teaching is conceived as a complex phenomenon which requires a methodological systematization, on the part of the teacher, looking to a progressive inclusion of the children. This study was carried out based on case study, class observation, filming, interviews, and so on. The study was conducted with a six-year-old class and their teacher, a seasoned kindergarten teacher who employs textual genres in her everyday practice. The classes that showed reading and writing as a dynamic process in which the material read and written allowed for knowledge generation through the participants interaction were analyzed. The children who still could not read and write were capable of reading and writing under the intervention of their teacher. The study made for an understanding of how the employment of authentic materials in the classrooms allows for a more meaningful learning and tune students in to a reality out of the school. Keywords: literacy, reading and writing skills, textual genres, props and intervention.